Analysis of Update Mapping in Science Learning Media Research: Bibliometric Analysis Based on Google Scholar Data - Sigit Subagja; Didit Ardianto; Bibin Rubini (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
This article presents a review of bibliometric analysis on the topic of science learning media research. The aim of this research is to identify relevant research and the latest research on the research topic being analyzed. The method used in this research is descriptive quantitative with bibliometric data approach. Research data collection is carried out on the Google Scholar page with the help of Publish or Perish (PoP) software using the keyword "science learning media". Search is limited to the 2019-2021 range and the number of search results is limited to 100. Data analysis and visualization using VOSviewer software. The result is the number of article citations is 328 citations with an average of 164 citations/year and 3.64 citations/articles. IOPSCIENCE is the most productive publisher with the highest number of articles, which is 23 articles. Bibliometric visualization of network maps based on text-mining analysis resulted in 24 interconnected words grouped into 4 clusters and network maps based on the authors of the Co-authorsip showed that Alpusari and Hermita were the authors who had the most related with other authors in the topic of science learning media research.